2008
DOI: 10.1186/1743-422x-5-155
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid Hepatitis A Virus (HAV) titration assay based on antibiotic resistance of infected cells: evaluation of the HAV neutralization potency of human immune globulin preparations

Abstract: Background: Hepatitis A virus (HAV), the causative agent of acute hepatitis in humans, is an atypical Picornaviridae that grows poorly in cell culture. HAV titrations are laborious and timeconsuming because the virus in general does not cause cytopathic effect and is detected by immunochemical or molecular probes. Simple HAV titration assays could be developed using currently available viral construct containing selectable markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…It was reported that an antibiotic resistance titration assay (ARTA) is useful for HAV neutralization including virus‐receptor interaction 33,34 . We also tested the effects of amantadine against HAV IRES of clinical isolates and confirmed the effects against fulminant hepatitis clones.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…It was reported that an antibiotic resistance titration assay (ARTA) is useful for HAV neutralization including virus‐receptor interaction 33,34 . We also tested the effects of amantadine against HAV IRES of clinical isolates and confirmed the effects against fulminant hepatitis clones.…”
Section: Resultsmentioning
confidence: 70%
“…It was reported that an antibiotic resistance titration assay (ARTA) is useful for HAV neutralization including virus-receptor interaction. 33,34 We also tested the effects of amantadine against HAV IRES of clinical isolates and confirmed the effects against fulminant hepatitis clones. Recently, it was reported that new acridines and hydrazones derived from cyclic b-diketone have stronger antiviral activities against HAV than amantadine.…”
Section: Amantadine Has Inhibitory Effect On Clinical Isolate-derivedmentioning
confidence: 66%
“…Subsequent methods developed to assay HAV in tissue culture include the radioimmunofocus assay (RIFA) (Lemon et al 1983), in situ RIFA and the fluorescent focus assay (Siegl et al 1984); all three procedures have been commonly used to monitor the production of HAV antigen as an indirect indicator of viral growth (Purcell et al 1976, Siegl et al 1984. Few assay methods have been developed for HAV titration (Lemon et al 1983, Richards & Watson 2001, Villar et al 2004, Konduru et al 2008.…”
mentioning
confidence: 99%
“…HAV grows extremely slowly in cell culture and often replicates without any visible cytopathic effect, unlike other members of the family Picornaviridae such as poliovirus and human rhinovirus (Gauss-Muller et al, 1986;Stapleton et al, 1993;Zahn et al, 1984). Various in vitro assays have been developed to assess the activity of anti-HAV neutralizing antibodies; however, these assays are often lengthy (requiring 8 days-3 weeks) (Beales et al, 1996;Cao et al, 2008;Kim et al, 2004;Konduru et al, 2008) and may be more labour-intensive than microplate-based assays. Thus, a simpler and more rapid method for detecting and quantifying HAV neutralizing antibodies, perhaps amenable to a higher-throughput format, would be beneficial.…”
Section: Introductionmentioning
confidence: 99%